The Values of Multicultural Education in Tali Dua Music in Batang Dua Island, Ternate, North Maluku - Salu, Vega Ricky; Triyanto, Triyanto; Wadiyo, Wadiyo (Catharsis, 2018)
Multicultural Education in Indonesian context has a very significant role and function. The variety of cultures also exists in Batang dua island. The ethnic groups in North Maluku are Loloda, Tobaru, Ternate, Javanese, Minahasan, Ambonese, Batak and many more. The purpose of this research is to explain the values of multicultural education in Tali Dua traditional music in Ternate, North Maluku. The research method used is qualitative approach. The technique of collecting data used are observation, interview, and document study. The data validity is checked by applying triangulation technique. Then, the data are analyzed by using data verification, data reduction and data presentation. The result of the study showd that Tali Dua music has multicultural values which are very important for the development of Indonesia, seen in the function of the music either in wedding events or in the lawidi tradition.